Education in Academic Emergency Medicine During the COVID-19 Pandemic – Our Experience From an Ongoing Crisis - Mueller, Matthias; Schriefl, Christoph; Holzer, Michael; Roeggla, Martin; Laggner, Anton N.; Ettl, Florian (Frontiers in Public Health, 2020)
Background: The COVID-19 pandemic has resulted in the suspension of the entire teaching program at the Medical University of Vienna till the end of the summer semester. As the department that is responsible for emergency medicine teaching, we adapted the program to continue the courses and maintain the learning progress. Our objective is to evaluate the number of courses conducted and report the methods used. Methods: Teaching was measured as credit hours per week (CHW) in accordance with the university’s prospectus. One CHW represents 15 academic hours (45 minutes) in one semester. Webinars were conducted using the CISCO Webex Events®, Webex Training®, and ZOOM®. The Moodle® was utilized for resuscitation courses. Results: Courses and clerkships equivalent to 80.2 out of 101.4 CHW (79.1%) could be held during the ongoing crisis in the summer semester. Courses in the winter semester were all completed. In the human medicine curriculum, 73.7 out of 94.9 CHW (77.7%) could be conducted. In the case of emergency lectures for the dentistry curriculum, all courses were conducted through webinars (6.5 CHW, 100%). After calculating the exact number of students in each class, it has been determined that courses and clerkships equivalent to 78.7% could be conducted. Conclusion: Despite the challenge of preparing for the treatment of numerous patients during the ongoing pandemic, we could shoulder a majority of our teaching responsibilities. Although sufficient skill training could not be imparted under these circumstances, we could provide sufficient theoretical knowledge to allow students to continue studies.